Peran Guru Sebagai Agen Perubahan di Sekolah Dan Masyarakat - Yasin, Muhammad; Ikhsan, M.; Hawa, Ewiniarti; Dewi Nadila, Amanda (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The role of teachers in the era of globalization and modernization is not only limited to the learning process in the classroom, but also includes a strategic role as an agent of change both in the school environment and society. Teachers have a major influence in transferring knowledge, values, and skills needed to face dynamic social change. As agents of change, teachers are required not only to be adaptive to technological developments and shifts in social values, but also to be drivers of positive transformation in schools and surrounding communities. This research aims to explore the role of teachers as agents of change and analyze the strategies and challenges they face in carrying out this role. Through a qualitative approach, this research explores teachers' perspectives regarding their role in building a conducive learning environment, as well as their contribution to society in instilling moral and social values. The research results show that teachers play a role as educators, motivators, facilitators and catalysts in forming positive character and culture in schools, as well as as role models and drivers of change in society. It is hoped that these findings can provide theoretical and practical contributions to the development of education and increase the social role of teachers as agents of change.